The evolution of fetal presentation during pregnancy: a retrospective, descriptive cross‐sectional study. (25th March 2015) - Ferreira, Jose C.P.; Borowski, Dariusz; Czuba, Bartosz; Cnota, Wojciech; Wloch, Agata; Sodowski, Krzysztof; Wielgos, Miroslaw; Wegrzyn, Piotr
Abstract We investigated changes in the frequencies of four primary types of singleton fetal lie/presentation for each gestational week from 18 to 39 weeks in a retrospective, cross‐sectional study which analyzed ultrasound examination records of fetal positions, in the outpatient prenatal diagnosis clinics in two cities in Poland. We calculated the prevalence and 95% confidence intervals for each type of lie/presentation. We then identified the gestational age after which no statistically significant changes in terms of prevalence were observed, by comparing the results at each week with the prevalence of cephalic presentation at 39+0 weeks, used as reference. A total of 18 019 ultrasound examinations were used. From 22 to 36 weeks of gestation, the prevalence of cephalic presentation increased from 47% (45–50%) to 94% (91–96%), before and after which times plateaus were noted. Spontaneous change from breech to cephalic is unlikely to occur after 36 weeks of gestation.